2018
DOI: 10.1002/jcp.27051
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tumor angiogenesis by microRNAs: State of the art

Abstract: MicroRNAs (miRNAs, miRs) are small (21-25 nucleotides) endogenous and noncoding RNAs involved in many cellular processes such as apoptosis, development, proliferation, and differentiation via binding to the 3'-untranslated region of the target mRNA and inhibiting its translation. Angiogenesis is a hallmark of cancer, which provides oxygen and nutrition for tumor growth while removing deposits and wastes from the tumor microenvironment. There are many angiogenesis stimulators, among which vascular endothelial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 138 publications
(194 reference statements)
0
61
0
Order By: Relevance
“…Angiogenesis (microvascular formation) is a cancer maker that provides substances necessary for tumour growth while removing waste and sediment from the tumour microenvironment. 53 In a previous study, in vitro capillary network formation experiments using HBMECs revealed that 10 μM ivermectin completely eliminated the ability of HBMECs to form tubular structures, confirming the effect of ivermectin against angiogenesis. 24 In conclusion, these findings indicate that ivermectin is a powerful angiogenesis inhibitor that also inhibits proliferation and induces apoptosis in HBMECs.…”
Section: Other Novel Molecular Mechanisms Of Ivermectin Ivermectin Ismentioning
confidence: 56%
See 1 more Smart Citation
“…Angiogenesis (microvascular formation) is a cancer maker that provides substances necessary for tumour growth while removing waste and sediment from the tumour microenvironment. 53 In a previous study, in vitro capillary network formation experiments using HBMECs revealed that 10 μM ivermectin completely eliminated the ability of HBMECs to form tubular structures, confirming the effect of ivermectin against angiogenesis. 24 In conclusion, these findings indicate that ivermectin is a powerful angiogenesis inhibitor that also inhibits proliferation and induces apoptosis in HBMECs.…”
Section: Other Novel Molecular Mechanisms Of Ivermectin Ivermectin Ismentioning
confidence: 56%
“…24 Several miRNAs have been revealed to influence the expression of VEGF and its tyrosine kinase receptors downstream of hypoxiainducible factor 1 (HIF-1) in tumour angiogenesis. 53 Whether these miRNAs are targets of ivermectin remains to be confirmed, but the probable mechanisms have not been studied.…”
Section: Other Novel Molecular Mechanisms Of Ivermectin Ivermectin Ismentioning
confidence: 99%
“…MiRNAs are increasingly being investigated as potential antiangiogenic small molecule drugs for tumor therapy (Goradel et al, 2019). In this study, bioinformatic analysis was used to identify miRNAs that could potentially target ALK1, and 12 candidate miRNAs were selected.…”
Section: Discussionmentioning
confidence: 99%
“…Among the regulators of tumor angiogenesis are microRNAs (miRNAs), which can act as anti-angiogenic but also as pro-angiogenic factors [6,7]. miRNAs are small (21-25 nucleotides) non-coding RNAs that negatively regulate gene expression [8].…”
Section: Introductionmentioning
confidence: 99%